THE DEVELOPMENT AND DISSEMINATION OF HADITH IN KHURASAN: A HISTORICAL-CRITICAL ANALYSIS - Maghfiroh, Fadila; arifah, Afro Anzali Nurizzati Arifah (LPPM UIN Syekh Wasil Kediri, 2025)
This study examines the development and dissemination of hadith in the Khurasan region, one of the most significant centers in the history of Islamic civilization. Hadith entered Khurasan during the caliphate of Uthman ibn Affan RA, coinciding with the Muslim conquest of the region. Although the initial transmission of hadith was limited due to the deaths of several Companions in battle, the growth of hadith studies did not cease. The generations of tabi‘in and tabi‘al-tabi‘in played a crucial role in revitalizing the hadith tradition in Khurasan, producing numerous renowned scholars recognized for their authority, such as Abdullah ibn alMubarak, Imam al-Bukhari, Imam Muslim, and al-Bayhaqi. Employing a qualitative method with a literature-based approach, this research draws from classical hadith collections, scholarly books, journals, and relevant articles. The findings indicate that Khurasan not only served as a hub for hadith teaching and transmission but also became the birthplace of various sub-disciplines of hadith, including ‘Ilal al-Hadith, Jarh wa Ta‘dil, and Tarikh al-Ruwah. Consequently, Khurasan played a pivotal role in preserving the authenticity of hadith and shaping the intellectual networks of the Islamic world in the East.